Microbiome–transcriptome analysis reveals that dietary supplementation with macleaya cordata extract alters multiple immune pathways with minimal impact on microbial structure - Wu, Jian; Zhang, Xiaoli; Zhou, Chuanshe; Jiao, Jinzhen; Tan, Zhiliang (Frontiers in Cellular and Infection Microbiology, 2023)
Background As a potential antibiotic alternative, macleaya cordata extract (MCE) has anti-inflammatory, antioxidant, and antimicrobial properties. This study was conducted to access the impact of MCE supplementation on the gut microbiota and its interplay with the host in young goats. Thirty female black goats with similar body weight (5.63 ± 0.30 kg) were selected and randomly allotted into one of the three diets: a control diet (Control), a control diet with antibiotics (Antibiotics, 21mg/kg/d vancomycin and 42mg/kg/d neomycin), and a control diet with MCE (MCE, 3.75 % w/w premix).Principal coordinate analysis of microbial community showed that samples of Antibiotic clustered separately from both of Control and MCE (P < 0.001). And the random forest analysis revealed that, in comparison to the Control group, the impact of Antibiotics on the microbiota structure was more pronounced than that of MCE (numbers of featured microbiota, 13 in Antibiotics > 6 in MCE). In addition, the pathways of significant enrichment either from DEGs between Antibiotics vs Control or DEGs between MCE vs Control were almost identical, including Th17 cell differentiation, butanoate metabolism, T cell receptor signaling pathway, intestinal immune network for IgA production, antigen processing and presentation, and ABC transporters. Furthermore, an integrative analysis indicated that significant positive correlations (P < 0.05) were observed between HEPHL1 and the featured biomarkers Atopostipes, Syntrophococcus, Romboutsia, and Acinetobacter in the MCE group.Conversely, several significant negative correlations (P < 0.05) were identified between HEPHL1 and the featured biomarkers Clostridium_XlVa, Phascolarctobacterium, Desulfovibrio, Cloacibacillus, Barnesiella, Succinatimonas, Alistipes, Oscillibacter, Ruminococcus2 and Megasphaera in the Antibiotics group.Collectively, the analysis of microbiome-transcriptome data revealed that dietary supplementation with macleaya cordata extract produced significant alterations in multiple immune pathways, while having minimal impact on microbial structure.